Pengembangan media pembelajaran literasi digital interaktif pada materi persebaran flora dan fauna - Titip Prayoga; Yusuf Suharto; Didik Taryana (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2022)
The lack of interactive learning media in learning Geography builds researchers’ intention to create effective learning media used in the learning process. One of the appropriate learning media with current technological advances is interactive digital literacy learning media. The development of this digital literacy learning media has the aim of improving the quality of Geography learning. At this media development stage includes eight development sequences including: (1) needs analysis, (2) preparation of learning media objectives, (3) collection of material items, (4) formulation of product assessment instruments, (5) making media, (6) implementation of the test, (7) revision, and (8) the final product. The product validity test was carried out by three experts, the first being a media expert who scored 100 percent with the validity criteria "valid", the second material expert got a score of 75.5 percent with the validity criteria "quite valid" and the last one the geography teacher got a score of 91.4 percent with "Valid" Validity Criteria. The effectiveness test was carried out at SMAN 1 Kalitidu Class XI IPS 1, totaling 31 students. The class was divided into two control and experimental groups to test the effectiveness of the learning media, and the result was that the experimental class gain score was greater than the control class, which was 27.5 while the control class gain score was 19. So, it can be stated that this interactive digital literacy learning media is valid and effective used by students. Kurangnya media pembelajaran interaktif dalam pembelajaran Geografi membangun niat peneliti untuk menciptakan media pembelajaran yang efektif digunakan dalam proses pembelajaran. Salah satu media pembelajaran yang tepat dengan kemajuan teknologi saat ini adalah media pembelajaran literasi digital interaktif. Pengembangan media pembelajaran literasi digital ini memiliki tujuan untuk meningkatkan kualitas pembelajaran Geografi. Pada tahap pengembangan media ini meliputi delapan urutan pengembangan meliputi: (1) analisis kebutuhan, (2) penyusunan tujuan media pembelajaran, (3) pengumpulan butir materi, (4) perumusan instrument penilaian produk, (5) pembuatan media, (6) pelaksanaan tes, (7) revisi, dan (8) produk akhir. Uji kevalidan produk dilakukan oleh tiga ahli yang pertama ahli media mendapatkan nilai 100 persen dengan kriteria kevalidan “valid”, yang kedua ahli materi mendapatkan nilai 75,5 persen dengan kriteria kevalidan “cukup valid” dan yang terakhir guru Geografi mendapatkan nilai 91,4 persen dengan kriteria kevalidan “valid”. Uji keefektifan dilakukan di SMAN 1 Kalitidu kelas XI IPS 1 yang berjumlah 31 siswa. Kelas dibagi menjadi dua kelompok kontrol dan eksperimen untuk menguji keefektifan media pembelajaran dan hasilnya gain skor kelas eksperimen lebih besar dibanding kelas kontrol yakni sebesar 27,5 sedangkan gain skor kelas kontrol sebesar 19. Jadi, dapat dinyatakan media pembelajaran literasi digital interaktif ini valid dan efektif digunakan oleh siswa.